Pengaruh Perencanaan Strategis di Klinik Basmalah Medika terhadap Mutu Pelayanan dan Kepuasan Pasien - Dermawan, Diki Tri Bagus; Kosasih, Kosasih; Utojo, Widjajanti; Asnar, Etty Sofia Mariati; Yuliaty, Farida (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The Inpatient Clinic (KRI) Basmalah Medika is an Islamic-themed clinic with the advantage of full accreditation, BPJS collaboration, and medical staff meeting Ministry of Health standards. Before implementing strategic planning, the clinic faced issues such as non-standard hazardous waste (B3) management, suboptimal drug stock management, and poorly organized human resources. Through service quality-based strategies aligned with Ministry of Health standards, the clinic successfully improved service quality and patient satisfaction. This study employed a descriptive qualitative method. Strategic planning plays a crucial role in defining the organization’s direction and ensuring that management operates in alignment with its goals. Prior to its implementation, the clinic's management lacked clear direction. The effective implementation of strategic planning has been proven to enhance service quality, encompassing five dimensions: tangible, empathy, reliability, responsiveness, and assurance. The improvement in service quality is evident from the retention of existing patients, an increase in new patients, higher capitation, and minimal patient complaints. Strategic planning at KRI Basmalah Medika has successfully managed resources effectively and achieved quality standards. The quality validation conducted by experts indicates excellent standards. High quality leads to increased patient satisfaction and strengthens the clinic's reputation within the community.